Ars scribendi. Writing Implements Discovered in the Legionary Fortress of Potaissa - VARGA, Timea; CHIOREAN, Paul (Studia Universitatis Babeș-Bolyai Historia, 2020)
Other than the already renowned 25 tabulae ceratae discovered at Alburnus Maior, the province of Dacia has also yielded numerous monumental or minor inscriptions, including both basic, as well as more informative graffiti. In the legionary fortress of Potaissa, besides numerous monumental inscriptions, eight tegulae scriptae, as well as a few ownership marks, the presence of other written documents can be deduced both from the existence of certain specialized personnel and especially from the presence of writing implements dispersed in the commandment building, the military baths and the soldiers’ barracks. Thus, even though papyri, parchments or waxed tablets have not been preserved due to their perishable material, their use in the legionary fortress could be indirectly attested by the discovery of eight styli, two inkwells, three rulers, four seal boxes and six lead seals. Rezumat: Pe lângă deja bine cunoscutele 25 de tabulae ceratae descoperite la Alburnus Maior, în provincia Dacia s-au descoperit și numeroase inscripții monumentale sau minore, ce redau atât cuvinte simple, cât și texte mai informative. În castrul legionar de la Potaissa, pe lângă numeroase inscripții monumentale, opt tegulae scriptae și câteva mărci de proprietar, prezența altor documente scrise poate fi dedusă din existența personalului specializat în scris și mai ales din prezența instrumentelor de scris găsite în clădirea comandamentului, în băile militare și în barăcile soldaților. Astfel, chiar dacă fragmente de papirus, de pergament sau tăblițe cerate nu au fost descoperite, datorită materialelor perisabile din care erau făcute, utilizarea lor în fortificația legionară poate fi dedusă indirect prin descoperirea a opt styli, două călimări, trei liniare, patru capsule de sigilii și șase sigilii de plumb. Cuvinte cheie: instrumenta scriptoria, styli, călimări, litterati milites, Potaissa